THE EFFECTIVENESS OF USING POE (PREDICT-OBSERVE-EXPLAIN) STRATEGY ON STUDENTS’ LEARNING RESULT OF REACTION RATE CHAPTER IN SMA - Syamsiana, Frisca; Suyatno, Suyatno; Taufikurahmah, Titik (Universitas Negeri Surabaya, 2018)
. The purpose of this research is to describe the effectiveness of using POE strategy on students? learning result on the topic of the factors affecting reaction rate. The subjects of this research are 33 students of XI grade MIA 1 SMAN 1 Leces Probolinggo in 2016/2017 academic year. The data collecting techniques in this research were observation, test, and questionnaire. The results showed that the students?activities were student-centered learning and all students achieved the completeness of learning result in knowledge aspect. Based on those results, we could conclude that the implementation of POE strategy were effective to improve student?s learning result on the topic of factors affecting reaction rate.